Melancolia: da bile negra à sombra do objeto que encobre o Eu - Santos, Marcela Cristina dos (2020)
Melancholy has been discusses in countless ways throughout history, often getting different names, which points to an attempt to differentiate it conceptually. Our proposal is to investigate melancholy over time, making it possible to have a historical an